The Validity and Reliability of Pain Instruments In Patients With Decreased Level Of Consciousness: A Literature Review - Asriyanto, Luthfi Fauzy; Chayati, Nur (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Pain is an unpleasant experience that produces a detrimental effect on patients. The quality of pain management is influenced by an accurate pain assessment. However, a pain assessment in patients with a decreased level of consciousness is still a big challenge for nurses. Currently, there is no standard instrument for assessing pain in this population. This study aims to determine a valid and reliable pain instrument for pain assessment in patients with a decreased consciousness level. Our study was a literature review guided by Preferred Reporting Items for Systematic Reviews and Meta-Analysis. The Systematic search was conducted in PubMed, Science Direct, Scopus, SAGE, Taylor Francis, dan ProQuest using the keywords of “Pain Assessment” and “Loss of Consciousness”. The inclusion criteria were observational or experimental design articles, adult patients, and studies of patients with a decreased level of consciousnessbut not in a coma. The bibliography search yielded 861 articles. Through the selection process, seven articles were found to meet the eligibility. The results of the study show that pain instrument based on behavioral observations has better validity than the physiological indicator. All studies using pain instruments recommend the Critical-Care Pain Observational Tool as a valid and reliable instrument for pain assessment in patients with verbal communication disabilities. Facial expression is the most relevant indicator in assessing pain intensity changes. The results of this study increase the opportunity for nurses to build scientific evidence to improve the quality of pain management. Abstrak: Nyeri merupakan sebuah pengalaman tidak menyenangkan yang mengakibatkan efek buruk pada pasien. Kualitas penatalaksanaan nyeri dipengaruhi oleh penilaian nyeri yang akurat. Penilaian nyeri pada pasien dengan penurunan tingkat kesadaran masih menjadi tantangan besar bagi perawat. Saat ini belum terdapat instrumen standar yang digunakan dalam penilaian nyeri pada populasi pasien dengan penurunan tingkat kesadaran. Penelitian ini bertujuan untuk menentukan validitas dan reliabilitas instrumen nyeri pada pasien dengan penurunan tingkat kesadaran. Penelitian ini merupakan literature review yang mengacu pada pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analysis. Penelusuran sistematis dilakukan melalui database jurnal PubMed, Science Direct, Scopus, SAGE, Taylor Francis, dan ProQuest menggunakan kata kunci “Pain Assessment” and “Loss of Consciousness”. Kriteria inklusi penelitian meliputi artikel dengan metode observasi atau eksperimen, melibatkan pasien dewasa, dan penelitian dilakukan terhadap pasien dengan penurunan tingkat kesadaran, namun bukan dalam keadaan koma. Penelusuran pustaka menghasilkan 861 artikel. Melalui proses seleksi, didapatkan tujuh artikel yang memenuhi kriteria kelayakan review. Hasil review artikel menunjukkan bahwa instrumen nyeri berbasis observasi perilaku memiliki validitas lebih baik dibanding indikator fisiologis. Semua artikel penelitian yang menggunakan instrumen nyeri merekomendasikan Critical-Care Pain Observation Tool (CPOT) sebagai instrumen yang valid dan reliabel dalam penilaian nyeri terhadap pasien dengan ketidakmampuan komunikasi verbal. Ekspresi wajah merupakan indikator paling relevan dalam menilai perubahan intensitas nyeri. Hasil review ini meningkatkan peluang perawat dalam membangun bukti ilmiah guna meningkatkan kualitas penatalaksanaan nyeri.